2010
DOI: 10.1371/journal.pone.0010757
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Basis for the Gender Differences in Murine Paracoccidioides brasiliensis Infection

Abstract: This study aimed to investigate the immunological mechanisms involved in the gender distinct incidence of paracoccidioidomycosis (pcm), an endemic systemic mycosis in Latin America, which is at least 10 times more frequent in men than in women. Then, we compared the immune response of male and female mice to Paracoccidioides brasiliensis infection, as well as the influence in the gender differences exerted by paracoccin, a P. brasiliensis component with carbohydrate recognition property. High production of Th1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 67 publications
(93 reference statements)
2
56
0
12
Order By: Relevance
“…Similarly, previous studies in adult female mice have shown that ovariectomy results in a reduced immune response to malaria and E or E + P supplementation rescued this defect (Cernetich et al 2006;Klein et al 2008). Ovariectomy also reduced the immune response to Bacillus brasiliensis in adult female rats (Pinzan et al 2010). Interestingly in our studies, HT did not restore the magnitude of the T-and B-cell responses to levels measured in intact animals.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, previous studies in adult female mice have shown that ovariectomy results in a reduced immune response to malaria and E or E + P supplementation rescued this defect (Cernetich et al 2006;Klein et al 2008). Ovariectomy also reduced the immune response to Bacillus brasiliensis in adult female rats (Pinzan et al 2010). Interestingly in our studies, HT did not restore the magnitude of the T-and B-cell responses to levels measured in intact animals.…”
Section: Discussionsupporting
confidence: 69%
“…[31][32][33][34][35][36] Males generally exhibit lower immune responses than females. 22,31,37 The phagocytic activity of macrophages and production of inflammatory cytokines are higher in females than in males.…”
Section: Discussionmentioning
confidence: 99%
“…33,[43][44][45] In P. chabaudi infection, ovariectomized female mice exhibit reduced production of the cytokines IL-12 and IFN-γ, leading to increased susceptibility. 24 However, in our study, ovariectomy in female mice caused low peak parasitemia and contributed to resistance against B. microti infection.…”
Section: Discussionmentioning
confidence: 99%
“…These results were confirmed using mice that had been submitted to gonadectomy followed by inverse hormonal reconstitution, where spleen cells derived from castrated males reconstituted with estradiol had produced higher levels of IFN-γ and lower levels of IL-10 than normal males in response to paracoccin stimulus. In contrast, spleen cells from castrated female mice that had been treated with testosterone produced more IL-10 and less IFN-γ than cells from normal females (Pinzan et al, 2010). In conclusion, these results reveal that the sexual hormones had a profound effect on the biology of immune cells, with estradiol favoring protective responses against P.brasiliensis infection.…”
Section: Production Of Cytokinesmentioning
confidence: 76%
“…Even though these cytokines have been implicated in the formation and maintenance of granuloma, some of them (IL-1, TNF-, IL-13 and TGF-) are also directly involved in fibrosis generation (Franco et al, 1998;Lopera et al, 2011;Naranjo et al, 2011;Wynn, 2007). Other authors, using both male and female mice in a PCM experimental model, have shown different immune responses that are gender-dependent with high production of Th1 cytokines and T-beta expression by the paracoccin-stimulated cultures of spleen cells from infected female mice; in contrast, cells from infected males produced higher levels of the Th2 cytokines and expressed GATA-3 (Pinzan et al, 2010). These results were confirmed using mice that had been submitted to gonadectomy followed by inverse hormonal reconstitution, where spleen cells derived from castrated males reconstituted with estradiol had produced higher levels of IFN-γ and lower levels of IL-10 than normal males in response to paracoccin stimulus.…”
Section: Production Of Cytokinesmentioning
confidence: 99%